2013
DOI: 10.1002/lary.23843
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile nasopharyngeal angiofibroma: A Systematic Review and Comparison of Endoscopic, Endoscopic‐Assisted, and Open Resection in 1047 Cases

Abstract: In this study, endoscopic resection had a significantly lower intraoperative blood loss and lower recurrence rate when compared to open resection. However, there was no difference in recurrence rate when analyzing the IPD and controlling for Radkowski/Sessions grading. Therefore, further large-scale studies may be required to fully elucidate treatment options.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
180
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 139 publications
(190 citation statements)
references
References 99 publications
8
180
0
2
Order By: Relevance
“…The study estimated residual tumor to be present in 7.7% of cases. Tumor recurrence rate was estimated to be 10%, which is consistent with the IPD cohort from Boghani et al (2013 3 This study, which comprised 162 patients, found that endoscopic JNA resection had a lower median blood loss as well as a lower number of complications compared to transpalatal or transmaxillary approaches. Chan et al (2013) reviewed their 18-year experience with all three approaches to JNA resection and found that blood loss, not surgical approach, was the only clinical factor that was significantly associated with complications from JNA surgery.…”
Section: Literature Reviewsupporting
confidence: 74%
See 2 more Smart Citations
“…The study estimated residual tumor to be present in 7.7% of cases. Tumor recurrence rate was estimated to be 10%, which is consistent with the IPD cohort from Boghani et al (2013 3 This study, which comprised 162 patients, found that endoscopic JNA resection had a lower median blood loss as well as a lower number of complications compared to transpalatal or transmaxillary approaches. Chan et al (2013) reviewed their 18-year experience with all three approaches to JNA resection and found that blood loss, not surgical approach, was the only clinical factor that was significantly associated with complications from JNA surgery.…”
Section: Literature Reviewsupporting
confidence: 74%
“…Recent systematic reviews and meta-analyses have provided a means to look at outcomes of JNA surgery in larger populations. Boghani et al (2013) published one such systematic review focusing on the outcomes of endoscopic, endoscopic-assisted, and open surgical approaches to JNA resection. A total of 85 studies comprising 1,047 surgical cases were identified.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Angiography and selective embolization are usually necessary in the preoperative stage for tumors considered highly vascular, like juvenile nasopharyngeal angiofibromas, but are also useful in other tumors, in order to reduce operative blood loss and improve visualization. The procedure should occur 24-48h prior to surgery, in order to minimize tumor revascularization 1,20 . Even though tumor resection was macroscopically complete, further oncological treatment and survey was necessary and recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Nasopharyngeal angiofibroma (NA) is a rare, non-encapsulated and highly-vascularized benign tumor that primarily affects adolescent males (1,2). Extremely few studies have described NA in elderly individuals; in our previous report of 162 cases from 1995 to 2012, all patients were male subjects ranging in age from 8-41 years (mean, 17.5 years) (3).…”
Section: Introductionmentioning
confidence: 99%